Effect of Heat Waves on Some Italian Brown Swiss Dairy Cows' Production Patterns - Maggiolino, Aristide; Landi, Vincenzo; Bartolomeo, Nicola; Bernabucci, Umberto; Santus, Enrico; Bragaglio, Andrea; De Palo, Pasquale (Frontiers in Animal Science, 2022)
Climate change is impacting worldwide efficiency and welfare standards in livestock production systems. Considering the sensibility to heat stress reported for different milk production patterns in Italian Brown Swiss, this study aims to evaluate the effect of heat waves (HWs)of different lengths on some milk production traits (fat-corrected milk, energy-corrected milk, protein and fat yield, protein percentage, cheese production at 24 h, and cheese yield). A 10-year dataset (2009–2018), containing 202,776 test-day records from 23,296 Brown Swiss cows, was used. The dataset was merged both with the daily maximum temperature–humidity index (THI) recorded by weather stations and with the daily maximum THI threshold for each trait in Italian Brown Swiss cows. The study considered 4 different HWs according to their length: 2, 3, 4, and 5 consecutive days before the test-day over the weighted THI threshold. Milk production traits were determined as the difference in losses compared to those after only 1 day before the test-day over the weighted maximum THI. All traits showed to be affected by HWs. Particularly, protein percentage losses increased from −0.047% to −0.070% after 2 consecutive days over the daily THI threshold, reaching −0.10% to −0.14% after 5 days (p < 0.01), showing a worsening trend with the increasing length of HWs. First parity cows showed to be more sensitive to HWs than other parity classes, recording greater losses after shorter HWs, compared to multiparous cows, for protein yield and, consequently, for cheese production at 24 h. This suggests a less efficient metabolic response to heat stress and exposure time in primiparous, compared to multiparous cows, probably due to their incomplete growth process that overlaps milk production, making it more difficult for them to dissipate heat. Although actions to mitigate heat stress are always needed in livestock, this study points out that often time exposure to warm periods worsens milk production traits in Brown Swiss cows.